Immigrant legalization: A dilemma between justice and the rule of law. (19th May 2022) - Song, Sarah; Bloemraad, Irene
Abstract: Immigrant legalization policies pose an ethical dilemma between justice and the rule of law. On the one hand, liberal democracies aspire to the principles of individual liberty and equality. Building on liberal ideals of justice, compelling arguments have been made for granting legal status and a path to citizenship to unauthorized migrants by virtue of the social ties they have developed, their contributions to the host society, and their vulnerability to exploitation. On the other hand, legalization poses a challenge to another important value, the rule of law, which requires government to operate within a framework of law in accordance with well-established public norms. Immigrant legalization programmes are said to undermine the rule of law because they reward lawbreaking, allow queue-jumping, and incentivize further unauthorized migration. This article clarifies each horn of the dilemma, focusing on rule of law arguments. We offer a critical reappraisal of immigrant legalization policies by reflecting on the normative meaning of the rule of law and by examining empirical evidence assessing the effects of legalization. Our central contention is that legalization policies can enhance the rule of law. We offer five rule of law arguments in support of legalization, which help to mitigate the dilemma between justice and the rule of law. We conclude by discussing some policy implications of our analysis.